Evaluation of the porous structure of Huadian oil shale during pyrolysis using multiple approaches. (1st January 2017) - Bai, Fengtian; Sun, Youhong; Liu, Yumin; Guo, Mingyi
Abstract: The porous structure of oil shale plays a vital role in heat transfer and mass transport of its pyrolysis, particularly for the flow behavior of shale oil and gas during in-situ conversion. It is essential to clarify the pore evolution and give a mathematical description of the complex pyrolysis. In this study, the effect of temperature (100–800 °C) on Huadian oil shale pyrolysis, and the creation and evolution of the pore structure during thermal treatment were investigated. The oil shale and residues were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, ultimate analysis, scanning electron microscopy, gas permeability measurement, nitrogen isothermal adsorption/desorption, and mercury intrusion porosimetry method. Furthermore, the fractal theory was employed to understand the complex pore characteristics of the samples. The results demonstrated that heating temperature obviously affect the chemical composition and pore evolution of the residues. The removal of volatile matter resulted in pores with enhanced rough and irregular surface; the permeability of the residues is significantly increased, particularly at 350–450 °C. In addition, the fractal dimension and average pore size demonstrated a good linear relationship.